2016
DOI: 10.1371/journal.pone.0163733
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Active versus Passive Recovery Periods during High Intensity Intermittent Exercise on Local Tissue Oxygenation in 18 – 30 Year Old Sedentary Men

Abstract: PurposeHigh intensity interval training (HIIT) has been proposed as a time-efficient format of exercise to reduce the chronic disease burden associated with sedentary behaviour. Changes in oxygen utilisation at the local tissue level during an acute session of HIIT could be the primary stimulus for the health benefits associated with this format of exercise. The recovery periods of HIIT effect the physiological responses that occur during the session. It was hypothesised that in sedentary individuals, local an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 69 publications
(91 reference statements)
6
45
0
Order By: Relevance
“…The purpose of the present study was to determine the effect of active recovery (cycling 1W/kg of body weight, ACT) and two passive recovery strategies (siting, PAS and sitting with compression calf sleeves, PAS+CS) on changes in blood lactate clearance, acid-basis and subsequent cycling performance VOLUME 14 | ISSUE 2 | 2019 | 407 parameters. Previous research has documented that the importance of active and passive recovery does exist and can have benefits for athletes (Frikha et al, 2016;Kriel et al, 2016;Mika et al, 2016;Wahl et al, 2014;Wahl et al, 2012). We support the superiority of active recovery choices methods over passive ones (with and without compression sleeves).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The purpose of the present study was to determine the effect of active recovery (cycling 1W/kg of body weight, ACT) and two passive recovery strategies (siting, PAS and sitting with compression calf sleeves, PAS+CS) on changes in blood lactate clearance, acid-basis and subsequent cycling performance VOLUME 14 | ISSUE 2 | 2019 | 407 parameters. Previous research has documented that the importance of active and passive recovery does exist and can have benefits for athletes (Frikha et al, 2016;Kriel et al, 2016;Mika et al, 2016;Wahl et al, 2014;Wahl et al, 2012). We support the superiority of active recovery choices methods over passive ones (with and without compression sleeves).…”
Section: Discussionsupporting
confidence: 76%
“…Current literature indicates that active recovery is the best strategy to sustain HICP (Wahl et al, 2013;Barnett, 2006;Spierer, Goldsmith, Baran, Hryniewicz, & Katz, 2004) and that the importance of both active and passive recovery strategies can have benefits for athletes (Frikha, Chaâri, Mezghanni, & Souissi, 2016;Kriel, Kerhervé, Askew, & Solomon, 2016;Mika et al, 2016;Wahl, Mathes, Achtzehn, Bloch, & Mester, 2014;Patrick Wahl, Bloch, Mester, Born, & Sperlich, 2012). Therefore, we aim to investigate the comparative effect of using compression calf sleeves with active recovery and passive rest on immediate recovery and high intensity repeated cycling performance.…”
Section: Introductionmentioning
confidence: 99%
“…Systemic vascular conductance at isotime during IE was greater compared with CLE, secondary to the lower mean arterial pressure during IE, thereby suggesting that reduced vascular resistance is most likely attributable to the repeated moderate‐intensity cycling periods (Kriel et al . 2016, 2019). Increased perfusion and muscle re‐oxygenation would be expected to enhance performance in locomotor muscles, potentially due to increased ATP and phosphocreatine resynthesis (Spencer et al .…”
Section: Discussionmentioning
confidence: 99%
“…Kriel et al 12,66 suggested that Δ[HHb] is potentially unaffected by changes in perfusion, blood volume and arterial hemoglobin concentration in high-intensity exercise, in contrast to Δ[O 2 Hb]. So, due to these characteristics, we will focus our discussion on the delta of deoxyhemoglobin responses (Δ[HHb]).…”
Section: Discussionmentioning
confidence: 99%